Credible signals of prospectus and the post listing performance of initial public offers / Lin Yong Tong - Lin , Yong Tong (2019)
The study of the performance of initial public offer (IPO) has been extensive in the past few decades because it is an intriguing topic for scholars and stakeholders, nevertheless the results obtained have been mixed. The contradictory results have been attributed to the different market rules applicable and the dynamic nature of the stock market. In 2017 alone, the average number of companies gone public globally is at a staggering rate of 6.4 IPO each trading day. To remain pertinent, regular studies are constantly needed to examine the determinants relevant to the performance of IPOs. Furthermore, continuous improvement to the research methodology is always well received. This thesis utilized a set of offer information unique to the Malaysian market recommended by the Securities Commission of Malaysia to investigate the factors that influence firm’s value. A total sample of 428 IPOs from Bursa Malaysia and market data between 2002 and 2017 are utilized in this study. The cross-sectional regression results demonstrate that five Signaling Theory variables and two Agency Theory variables have the powers to signal the future value of newly listed firms. These variables are the Public Issue ratio, Offer for Sale ratio, Retention ratio, High Premium dummy, High Investment Banker Reputation dummy, Staff ratio and the Bumiputera ratio. In addition, the level of Proceed Raised and the Initial Returns are found to be correlated to firm’s value. At the methodology front, apart from adopting two conventional methods to measure performance, a third experimental 12 days moving average method (MAC12) is introduced to add vigor to the study. The smoothing properties of MAC12 which cause the data to be less bias, has helped to produce findings that are more robust. In addition, this thesis analyzed and reported the findings of the Main Board, Second Board and the ACE IPOs collectively and individually up to three years post listing. By analyzing the samples of the three boards separately have proven to be meaningful as it helps to identify the origin of the relationship. The regression results demonstrated that the ACE market determinants have more influence over firm’s values. The results of this thesis based on up-to-date data will help scholars and stakeholders keep abreast with the current development thus, enable them to carry out their respective endeavors more effectively.